Internal genomic regions mobilized for telomere maintenance in C. elegans. Issue 1 (2nd January 2016) - Kim, Chuna; Sung, Sanghyun; Lee, Junho
ABSTRACT: Because DNA polymerase cannot replicate telomeric DNA at linear chromosomal ends, eukaryotes have developed specific telomere maintenance mechanisms (TMMs). A major TMM involves specialized reverse transcriptase, telomerase. However, there also exist various telomerase-independent TMMs (TI-TMMs), which can arise both in pathological conditions (such as cancers) and during evolution. The TI-TMM in cancer cells is called alternative lengthening of telomeres (ALT), whose mechanism is not fully understood. We generated stably maintained telomerase-independent survivors from C. elegans telomerase mutants and found that, unlike previously described survivors in worms, these survivors "mobilize" specific internal sequence blocks for telomere lengthening, which we named TALTs (templates for ALT). The cis -duplication of internal genomic TALTs produces "reservoirs" of TALTs, whose trans -duplication occurs at all chromosome ends in the ALT survivors. Our discovery that different TALTs are utilized in different wild isolates provides insight into the molecular events leading to telomere evolution.